Case studies for health information management - Schnering, Patricia (Clifton Park : Thomson Delmar Learning, 2007)
This five-program series focuses on applying critical thinking skills to real events and situations that occur in the workplace. Each case study dramatizes a real situation, provides a discussion checkpoint, and follows with an outcome that reflects how the scenario would be resolved in the real world. The programs align to the five health information management curriculum domains and include 20 case studies for review and discussion.
Keywords: DVD-ROMs.; Medical records -- Management -- DVD-ROMs.; Medical informatics -- DVD-ROMs.